(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2024)
Myths, legends, and fairy tales, what we will understand as ancestral narratives, are wonderful stories with a deep archetypal content that can be assumed as group referents of a symbolic order hidden in the collective unconscious, where they find meaning. This subject was studied exhaustively by the complex psychology of C.G. Jung and his disciple and colleague MarieLouise von Franz.